The relationship between technical and propedeutic education in reforms and counter-reforms in brazilian education (Revista Contexto & Educação, 2022)
This article aims to carry out a historical retrospective of legal provisions, relevant to education, which emerged between 1909 and 2021, which reveal the advances and setbacks regarding the articulation between professional education and propaedeutics. history of legal provisions, relevant to education, which emerged between 1909 and 2021, which reveal the advances and setbacks in terms of the articulation between professional education and propaedeutics. Based on information obtained through bibliographic and documentary research and through the analysis of the content of these devices, five cycles of educational policy were identified, important demarcations for understanding the limits placed on the effectiveness, in Brazil, of professional education as a public, democratic, unitary, polytechnic, omnilateral and emancipatory. It was found that there was no articulation between professional education and propaedeutic education in the first cycle. In the second, equivalences were identified, but without effective integration between these educational offers. In the third, the reestablishment of the logic of separation was observed. In the fourth cycle, advances in favor of the integration of vocational education with basic education and in the perspective of the unitary school and polytechnic and omnilateral training. In the fifth cycle, under way, there is an educational counter-reform aimed at reaffirming the logic of the structural duality of teaching. These five cycles showed how the contradictions between capital and work are reproduced in the sphere of educational legislation and give movement to the history of educational policies, revealing their advances and retreats and the strength of the State as a regulatory instance of conflicts.